Introduction of the Robbins Mobile Miner to Mount Isa Mines Limited - Malcolm J. McPhersqn; Neill T. J; Howarth D. F (The Australasian Institute of Mining and Metallurgy, 1986)
For many years Isa Mine has seen the need for a continuous mining machine which will economically cut hard rock. Tunnel borers are unsuitable due to the size and inflexibility of the machine and the shape of excavation mined. The design of roadheader type machines will not permit the use of the necessary cutting technology. in 1983 a joint project was undertaken by The Robbins Company and Mount Isa Mines Limited to develop and to trial a machine suitable for cutting hard rock in an operating mine. The project was based on the proven technology of raiseboring applied to horizontal development. The Mobile Miner was fabricated and trialled in a disused quarry in the U.S.A. during early 1984. Following these trials, the machine was transported to Mount Isa and commenced mining in September that year. The initial duty was to continue the development of a decline commenced by conventional mining for a conveyor system to serve the deeper southern areas of the 1100 copper orebody. This system will permit direct tipping of copper ore to a new crusher complex and conveying of the - crushed ore approximately 2 kilometres to the central hoisting shaft facilities. The Robbins Mobile Miner MM120-3001 uses a vertical rotating cutting wheel mounted on a horizontal swinging boom to excavate a nominally rectangular shaped heading. The cuttings are collected on an apron and conveyed back through the machine. The resulting excavation is smooth-walled with no blasting damage to the surrounding rock. This provides a safer working environment than does conventional drill and blast development mining. Ground support requirements are considerably reduced.